Penguatan Literasi Digital Tenaga Lepas Harian di Teaching Factory Pertanian Terpadu Politeknik Negeri Jember: Pengabdian - Ambarkahi, Ratih Puspitorini Yekti; Putra, Dhanang Eka; Wardani, Dyah Kusuma; Pratama, Fredy Eka Ardhi; A N, Ponti Primastuti; Savitri U, Pascawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to strengthen the digital literacy of daily workers who support the operational activities of the Integrated Agriculture Teaching Factory at Politeknik Negeri Jember through staged training and on-the-job mentoring integrated with the implementation of a fingerprint attendance system and digital work reporting. A quasi-experimental one group pretest–posttest design was applied to 25 daily workers employed in four TEFA lines, namely Smart Green House, Livestock, Innovation Garden, and Chrysanthemum units. Data were collected using a digital literacy test, perception questionnaires, observation sheets, and document reviews of attendance records and work reports before and after the intervention, then analyzed descriptively and complemented with a simple difference test. The results showed an increase in attendance compliance from 78.0% to 96.2%, a decrease in average tardiness from 14.0 to 9.1 minutes per shift, and a reduction in administrative recap SLA from 6.0 to 2.5 hours. Digital literacy scores increased from 55 to 77, accompanied by higher perception scores regarding task clarity, working hours transparency, incentive recording accuracy, and system ease of use.